Europa 2020 Strategy target in R&D sector: Visegrad group countries - Nina Bockova; Tomas Meluzin; Stanislav Skapa (Institute of Economic Research (IER), 2017)
This contribution analyses the relationship between Research and Development funding's and economic growth within the Visegrad Group during the period 2005-2014. The studied geographical area is regions NUTS 2 of the Visegrad Group. The indicators considered in this contribution are GDP per inhabitant, percentage of GERD performed by business sector and GERD as percentage of GDP. The econometric analysis show that R&D Intensity is an important driver of economic growth (R = 0.64) that is measured by GDP per inhabitant in PPS. This contribution is the result of a two-phase research fellowship funded by the Internal Grant Agency of the Brno University of Technology. The first phase project research produced a regression analyze with dependent variable GDP per inhabitant and independent variable GERD as percentage of GDP. In the second phase of the research were formulated econometric models. This contribution answers the following question: Can the Visegrad Group Members reach the Europa 2020 Strategy target in R&D, i.e. 3% of GDP to be invested into the R&D sector. This research uses Eurostat database for the analysis of the relationship between R&D funding by the business sector and the corresponding economic growth. The research is based on dependent variable GDP per capita and independent variables: GERD and R&D Intensity during the period 2005-2014. The fit goodness of the model is evaluated the determination coefficient, using T-test on the regression coefficients. The autocorrelation in the residuals is checked by applying the Durbin-Watson (D-W) test. The statistical analyze is performed by using Stepwise Multiple Regression in software STATISTICA 12. Main result of research provides relationship between economic growth measured by GDP per inhabitant and R&D expenditures as percentage of GDP. The studied statistical data set is 38 NUTS 2 regions in Visegrad Group. If the Visegrad Group regions will the 3% target then GDP PPS per inhabitant in equal to 29,276. The result of the research can be used for the Visegrad Group governments.
Keywords: O11; O47; O57; 330; economic growth; Visegrad Group; comparative study; regression analysis; Europe 2020 strategy